The way forward with social justice in Islamic economics - Rahim, Shafinah; Mohd Yusop, Mohd Mahyudi (Penerbit KUIS, 2023)
In this conceptual paper, the authors attempt to revive a critical yet fortuitously overlooked idea of justice (al-adl) in the Islamic academic debates. Given its direct and far-reaching effect on the realization of the Maqasid Shariah, the present work begins with evidences of specific emphasis on social justice in the Holy Quran as well as the tradition of Prophet Muhammad (S.A.W) highlighting the relationships between al-adl, al-haqq (truth) and al-qist (equity). Followed by, key literary works by both the past and contemporary Muslim scholars passionate about the subject matter of justice in general. Ultimately, the paper involves a 3R; recollect, refine and restore approach to bridging the theoretical views of social justice to its rightful implementation in forms of economic policies in Malaysia. The underlying short run goal of this research is to motivate others with similar interests to continue seeking solutions within the Turath. The longshot being the added knowledge and better appreciation of the understanding of justice as central to a moral economy, progressing to improved decision making and effective action plans.